2019
DOI: 10.1128/mbio.02708-18
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms, Detection, and Relevance of Protein Acetylation in Prokaryotes

Abstract: Posttranslational modification of a protein, either alone or in combination with other modifications, can control properties of that protein, such as enzymatic activity, localization, stability, or interactions with other molecules. N-ε-Lysine acetylation is one such modification that has gained attention in recent years, with a prevalence and significance that rival those of phosphorylation. This review will discuss the current state of the field in bacteria and some of the work in archaea, focusing on both m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 229 publications
(257 reference statements)
1
101
0
1
Order By: Relevance
“…Although both effects of acetyl-P have been convincingly demonstrated, their impact on cellular physiology is not fully elucidated, so far. Protein acetylation in E. coli has been studied on a global scale and acetylation of central metabolic enzymes is currently discussed as a mechanism to control metabolic fluxes (Weinert et al, 2013;Kuhn et al, 2014;Carabetta and Cristea, 2017;Nakayasu et al, 2017;Brunk et al, 2018;Christensen et al, 2019;VanDrisse and Escalante-Semerena, 2019). Besides such global effects, for a number of proteins an impact of acetylation on activity was shown (Wolfe, 2016;Carabetta and Cristea, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although both effects of acetyl-P have been convincingly demonstrated, their impact on cellular physiology is not fully elucidated, so far. Protein acetylation in E. coli has been studied on a global scale and acetylation of central metabolic enzymes is currently discussed as a mechanism to control metabolic fluxes (Weinert et al, 2013;Kuhn et al, 2014;Carabetta and Cristea, 2017;Nakayasu et al, 2017;Brunk et al, 2018;Christensen et al, 2019;VanDrisse and Escalante-Semerena, 2019). Besides such global effects, for a number of proteins an impact of acetylation on activity was shown (Wolfe, 2016;Carabetta and Cristea, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ likely that these compounds arise non-enzymatically, possibly by a reaction with acetyl-CoA. Such reactions are known to occur under relatively basic conditions within cells or in vitro 36 . It is possible that the ATP sulfurylase overexpressing seeds either contained higher levels of acetyl-CoA or that the internal pH or other conditions were more conducive for the reaction to occur.…”
Section: Discussionmentioning
confidence: 99%
“…For example, acetylation was long considered rare in Archaea. Recently, some studies have reported that acetylation is essential for the viability of haloarchaea [23,24]. Moreover, N-terminal protein acetylation is common in Eukaryotes and Archaea but very rare in Bacteria [25].…”
Section: Post-translational Modifications (Ptms) In Archaeamentioning
confidence: 99%